Kontrasepsi Oral Dan Resiko Tromboemboli - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT Contraception protects against pregnancy. The most popular one is oral contraception (pills). However, this contraception suggested has a harmful side effect. Called thromboemboli. The relationship between oral contraception and the increased risk of thromboemboli is through the intravascular coagulation. This intravascular coagulation stimulates thrombus formation, but this phenomenon doesn't occur in all woman who take oral contraception. Thrombus formation mostly related on estrogen dose and its combination. The role of hereditary factors must be kept in mind. That's why taking family history, venous disease or coagulation factors or inhibitors are so important.